UTILIZATION OF THE DIGITAL MEDIA EDUCANDY AS AN EFFORT TO IMPROVE STUDENTS’ GERMAN LANGUAGE COMPETENCE - Tri Edliani Lestari; Audrey Gabriella Titaley; Dwi Imroatu Julaikah; RR Maha Kalyana Mitta; Dwi Nur Cahyani Sri; Ajeng Dianing Kartika (LPPM Institut Pendidikan Nusantara Global, 2025)
The rapid development of digital technology in the Society 5.0 era demands innovation in foreign language learning. This study focuses on the utilization of the digital learning medium Educandy as an effort to enhance students’ competence and motivation in learning German. This topic is considered important because most teachers still use conventional teaching methods that tend to be less engaging and result in low student involvement. The research activities were conducted through a community service program at SMAN 1 Driyorejo, involving teachers and students of German language subjects. The method employed was descriptive qualitative with a participatory training model, which included the stages of preparation, training, mentoring, and evaluation. Data were obtained through observation, interviews, and documentation of activities. The results show that the implementation of Educandy in the learning process is able to improve students’ mastery of vocabulary and grammar, foster learning motivation, and encourage active participation in classroom activities. Teachers also experienced greater ease in the assessment process and in creating interactive learning media. These findings demonstrate that interactive digital media can serve as an effective, innovative, and relevant learning tool that meets the educational needs of the modern era. Thus, the use of Educandy contributes significantly to improving students’ language competence while simultaneously strengthening teachers’ digital pedagogical skills.